Thermoplastic matrix material influences on the mechanical performance of additively manufactured carbon-fiber-reinforced plastic composites. (April 2022) - Adeniran, Olusanmi; Cong, Weilong; Oluwabunmi, Kayode
Materials design and development continue to be more relevant as applications continue to rise for additively manufactured carbon-fiber-reinforced-plastic (CFRP) composites. Plastic matrixes bond and protect the fiber and help to transfer load through the composite to support intended applications. This makes it more necessary to understand the influences of thermoplastic matrixes on the mechanical performance of the composites fabricated through the additive manufacturing (AM) technique. This study investigated Acrylonitrile–Butadiene–Styrene (ABS) and Polyamide (PA) matrixes, which represent the bulk of the amorphous and semicrystalline engineering-grade thermoplastics matrixes, respectively, used in CFRP composite applications. Mechanical properties: tensile, compression, flexural, and thermal properties were examined, with the results showing the thermoplastic matrixes compositions and morphologies influences on the mechanical properties. The CF-PA was found to offer superior strength, ductility, and toughness because of their close-packed ordered lamellar matrix morphology, while the CF-ABS was found to offer superior modulus because of their loose morphology which more easily rearrange in reaction to stress upon elastic deformation. The mechanical properties results were reinforced by the fracture failure modes and the thermal analysis results which showed the CF-PA composite's ability to withstand higher mechanical performance and temperatures before failure.